Investigation of the Relationship Between Cortisol Hormone Response and Body Mass Index According to Bigorexia Levels in Sports Sciences Faculty Students - Tuğçe ORKUN ERKILIÇ, Ali Ozan ERKILIÇ, Bülent BAYRAKTAR (Cuestiones de Fisioterapia, 2025)
The aim of this study is to investigate the relationship between cortisol hormone response and body mass index (BMI) according to bigorexia levels in sports sciences faculty students. The study was conducted on 40 university students (20 female, 20 male) of different genders who study at the 3rd year Recreation Department of the Faculty of Sports Sciences at Bayburt University, do not have any health problems, and regularly engage in bodybuilding.